US technological collaboration for nonproliferation: key evidence from the Cold War. Issue 3 (4th May 2018) - Krige, John; Sarkar, Jayita
ABSTRACT: Although the existing international-relations scholarship argues that technological assistance in the nuclear domain increases the probability of nuclear proliferation, the historical account indicates otherwise. Congressional legislation for nonproliferation, economic sanctions, and poor state capacity—specifically, inept managerial capabilities of the recipient state—explain merely part of the puzzle, but overlook the role of positive inducements offered to impede nuclear proliferation. Historical evidence shows that the United States often provided technological assistance with the deliberate intent to inhibit proliferation. In other words, Washington employed its technological leverage to attain nonproliferation goals. American technological preponderance since the end of World War II made such an approach feasible. This study examines key Cold War cases—Israel/Egypt, India, and West Germany—where the United States offered technological assistance with the deliberate intent to stall nuclear proliferation, thereby underscoring the role of assistance for inhibitive ends.